Factors Associated with Newborn Asphyxia at Dr. Harjono Hospital, Ponorogo, East Java - Purwaningsih, Yustina; Dewi, Yulia Lanti Retno; Indarto, Dono; Murti, Bhisma (Journal of Maternal and Child Health, 2018)
Background: Asphyxia, or perinatal asphyxia, refers to oxygen deprivation during labor or delivery long enough to cause physical harm, and particularly brain damage. When birth asphyxia is severe, it can injure brain cells and cause potentially fatal conditions, including Hypoxic-Ischemic En